Beginner Non-Native Arabic Speakers’ Awareness in Kudus State Islamic College - Muhammad In'ami (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2015)
Arabic is the most important language to be learned for Muslims. Umar Ibn Khattab said: you all have to learn the Arabic language because it is part of your religion. no doubt that Arabic has many influences and functions. Learning Arabic since childhood becomes imperative for fathers and mothers until a child understands well the Arabic language and provide the easiness in understanding the Qur'an and Hadis. Parents should strive and prepare their children for this noble purpose. when the child is able to understand the Arabic language, parents have succeeded to educate him in creating a good family environment and emotional closeness between them. without their encouragement and guidance, then the children faces difficulties to understand Arabic fluently. Schools and teachers have an important role in this issue through school activities that support the development of the Arabic language. all directions and methods implemented by teachers to students will certainly influence the success in understanding Arabic.